Frontispiece: Structure‐Based Programming of Supramolecular Assemblies in Living Cells for Selective Cancer Cell Inhibition. Issue 40 (20th September 2021) - Hu, Liangbo; Li, Ying; Lin, Xinhui; Huo, Yucheng; Zhang, Hongyue; Wang, Huaimin
Abstract : Supramolecular Chemistry Structure‐based programming of supramolecular assemblies in living cells for selective cancer cell inhibition is reported by Huaimin Wang et al. in their Research Article on page 21807 .